Gauss’s Law and a Gravitational Wave - Olamide Odutola; Arundhati Dasgupta (Universe, 2024)
In this paper, we discuss the semi-classical gravitational wave corrections to Gauss’s law and obtain an explicit solution for the electromagnetic potential. The gravitational wave perturbs the Coulomb potential with a function that propagates it to the asymptotics.